2018
DOI: 10.1136/bmjopen-2018-023406
|View full text |Cite
|
Sign up to set email alerts
|

Implications of parental lifestyle changes and education level on adolescent offspring weight: a population based cohort study - The HUNT Study, Norway

Abstract: ObjectiveObesity tends to cluster in families reflecting both common genetics and shared lifestyle patterns within the family environment. The aim of this study was to examine whether parental lifestyle changes over time, exemplified by changes in weight and physical activity, could affect offspring weight in adolescents and if parental education level influenced the relationship.Design, setting and participantsThe population-based cohort study included 4424 parent-offspring participants from the Nord-Trøndela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
0
23
1
Order By: Relevance
“…ey contribute to the gain of the recommended 60 min/day MVPA [31][32][33]. However, other studies demonstrate a lack of relationship between these variables or show the presence of the relationship with leisure time PA [34][35][36]. In our study, there was no statistically significant difference between the groups of male and female adolescents regarding the parental education level and family income and gaining the recommended 60 min/day MVPA.…”
Section: Discussioncontrasting
confidence: 69%
“…ey contribute to the gain of the recommended 60 min/day MVPA [31][32][33]. However, other studies demonstrate a lack of relationship between these variables or show the presence of the relationship with leisure time PA [34][35][36]. In our study, there was no statistically significant difference between the groups of male and female adolescents regarding the parental education level and family income and gaining the recommended 60 min/day MVPA.…”
Section: Discussioncontrasting
confidence: 69%
“…In our study, students whose fathers’ schooling was longer than 9 years experienced greater improvement in their prosocial behavior. Interestingly, previous studies have found that parental education significantly affects children’s involvement in more physical activity [ 44 , 45 , 46 ]. Previous research has also focused on the impact of positive experiences of family intimacy on prosocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Both education as well as maternal weight status can possibly be improved through political measures. For instance, enabling access to higher education and health promotion programs to socially disadvantaged future parents may reduce the children’s risk of overweight/obesity [ 55 ]. Additionally, situational prevention promoting healthy lifestyles, e.g., in terms of taxing sugar-sweetened beverages [ 56 ] and fast food, as well as lowering of fruit and vegetable prices [ 57 ] has been shown to beneficially influence dietary behaviors.…”
Section: Discussionmentioning
confidence: 99%